2002
DOI: 10.1046/j.1445-2197.2002.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum calcium and trace elements in chronic cholelithiasis

Abstract: Higher biliary calcium and trace elements as well as a defective pH of gall bladder bile in patients with chronic cholelithiasis could be the underlying factor in the pathogenesis of gallstones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
5
16
0
Order By: Relevance
“…This result is comparable with previous studies [10]. Chloride ions are always present in biological fluids in human beings including the bile, which might get deposited in the form of sodium chloride salt along with major salts of the gallstones [24].…”
Section: Chloridesupporting
confidence: 92%
“…This result is comparable with previous studies [10]. Chloride ions are always present in biological fluids in human beings including the bile, which might get deposited in the form of sodium chloride salt along with major salts of the gallstones [24].…”
Section: Chloridesupporting
confidence: 92%
“…It has been reported that zinc salts that flocculate at physiological pH adsorb unconjugated bilirubin almost completely from unsaturated micellar bile salts solutions, which in turn favor the precipitation of unconjugated bilirubin [19]. Higher biliary calcium and trace elements as well as a defective pH of gallbladder bile in patients with chronic cholelithiasis could be the underlying factor in the pathogenesis of gallstones [20].…”
Section: Discussionmentioning
confidence: 99%
“…Saad Muhmood Hussain 1 *, Karim Alwan Al-Jashamy 2 with dietary habits and ethnicity (Pundir et al, 2001;Verma et al, 2002;Chandran et al, 2007). Other studies have shown that dietary intake of total calories in the form of carbohydrates and fats were associated with high triglyceride levels in gallstone patients (Lee et al, 2012).…”
Section: Determination Of Chemical Composition Of Gallbladder Stones mentioning
confidence: 99%